PENGARUH TINDAK LANJUT REKOMENDASI AUDIT DAN SISTEM PENGENDALIAN INTERNAL PEMERINTAH TERHADAP KINERJA PEMERINTAH DAERAH: PERAN OPINI AUDIT SEBAGAI VARIABEL PEMODERASI - Talitha Ulayya Isnadiya; Tri Jatmiko Wahyu Prabowo (Diponegoro Journal of Accounting, 2026)
This study aims to analyze the impact of follow-up on audit recommendations and the Government Internal Control System (SPIP) on local government performance, as well as to examine the role of audit opinions as a moderating variable. Local government performance is measured using the Human Development Index (HDI), poverty rates, spending effectiveness, and spending efficiency. This study employs a quantitative approach using secondary data obtained from the BPK audit reports, local government financial statements, and local government statistical data. The analytical methods used are multiple linear regression and Moderated Regression Analysis (MRA). The results indicate that the follow-up on audit recommendations and the implementation of the Internal Control System (SPIP) significantly influence local government performance. The follow-up on audit recommendations has a positive effect on the HDI, expenditure effectiveness, and expenditure efficiency, and a negative effect on the poverty rate. Additionally, the audit opinion moderates the effect of the follow-up on audit recommendations on local government performance but does not moderate the effect of SPIP on local government performance. These findings indicate that improvements in local government performance are influenced by the effectiveness of audit recommendation follow-up and the optimal implementation of SPIP as part of efforts to achieve accountable and effective governance.